Optimasi Penggunaan Energi Terbarukan pada Budidaya Lele Bioflok di Pandeglang dengan HOMER - Rudi Purwo Wijayanto; Ronald Akbar; Imam Arif Raharjo (Piston: Jurnal Teknologi, 2024)
The bioflock catfish farming method presents advantages in terms of enhancing feed efficiency and reducing chemical usage. However, it faces challenges in higher energy consumption compared to conventional methods. Additionally, not all farming locations are situated near residential areas and connected to the PLN grid; some are located in remote areas without PLN grid access. This study aims to assess the potential and effectiveness of renewable energy utilization using HOMER Pro for bioflock catfish farming in Pandeglang, West Java. Pandeglang has an average solar radiation intensity of 5.27 kWh/m²/day and an average wind speed of 4.99 m/s, making it suitable for the utilization of solar panels and wind turbines as renewable energy sources. A bioflock catfish farming operation with a capacity of 2 tons per cycle requires 13.14 kWh/day of energy, with a peak load of 1.74 kW. Using HOMER Pro, this study explores 11 scenarios with various generator configurations. The most optimal scenario involves the use of solar panels with a capacity of 1.58 kW combined with energy from PLN, resulting in a renewable energy utilization rate of 39.2%. The cost of energy produced in the optimal scenario is Rp 1,019.00/kWh, with an Internal Rate of Return (IRR) of 20%, a Return on Investment (ROI) of 16%, and a Break-Even Point (BEP) of 5 years. The best scenario yields a Net Present Cost (NPC) of Rp 81,100,000, which is 19% lower than the baseline scenario's NPC of Rp 100,000,000 over the 20-year project period.